Proceedings of the third conference localization and energy transfer in nonlinear systems (World scientific, 2003)
This conference was the third meeting organized in the framework of the European LOCNET project. The main topics discussed by this international research collaboration were localization by nonlinearity and spatial discreteness, and energy transfer (in crystals, biomolecules and Josephson arrays).